PENGOLAHAN PRODUK JAHE MERAH SIAP SEDUH: PENDEKATAN INOVATIF DALAM PEMBERDAYAAN KADER POSYANDU DAN PKK DI KELURAHAN LIMAU MANIH SELATAN KOTA PADANG - Yoneta Srangenge; Dira Hefni; Beba Shiami; Henny Lucida (Jurnal Hilirisasi IPTEKS, 2024)
The high prevalence of self-medication in Indonesia necessitates interventions to reduce the risk of medication errors. This study aimed to empower Posyandu and Family Welfare Empowerment (PKK) cadres in Limau Manih Selatan Village through training in processing red ginger into ready-to-brew beverages, thereby enhancing community health and local economic development. The activity was conducted on September 9, 2023, at the Griya Permai Housing Posyandu, Limau Manih Selatan Village, Padang. The methods used included lectures, demonstrations, hands-on practice, and discussions. The training material covered the rational use of herbal medicines, the processing of red ginger, and how to produce quality products. Participants, comprising Posyandu cadres, PKK members, and the general community, were selected based on their roles within the community. The implementation of the activities resulted in a significant increase in knowledge and skills in red ginger processing and the rational use of herbal medicines among the 43 participants. Participants successfully produced ready-to-brew red ginger beverages that met quality standards. In addition to enhancing understanding of the safe use of traditional medicines, the training also changed public perceptions regarding herbal treatments. Participants showed high enthusiasm and provided positive feedback, expressing a desire for future training sessions. It can be concluded that this training was effective in empowering health cadres and improving their knowledge and skills in traditional medicine processing. For sustainability, it is recommended to continue monitoring and developing local businesses from the ready-to-brew red ginger products. Local village authorities and the government are expected to support this program to expand its impact, ultimately improving community health and promoting sustainable local economic development.